Investors’ awareness towards commodities market with reference to GUNTUR city, Andhra Pradesh - Hymavathi, CH; Koneru, Kalpana (International Journal of Engineering and Technology, 2018)
Commodity market is observed as an avenue to invest directly in trading markets. The study has aimed to evaluate investors trading habits, goals of investors, literacy and awareness level and emotional risk tolerance. Samples of 219 respondents are taken for this study. The study concludes the main aim of the investor to increase their wealth through commodity market which is one of the extended avenues for diversification.Â
Keywords: Trading Market; Investors; Commodity Market.